PENGARUH RENDAM KAKI MENGGUNAKAN AIR REBUSAN SERAI DAN GARAM TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI DESA SAMPALI KECAMATAN PERCUT SEI TUAN - Darius Setiaman Zamasi; Hizkianta Sembiring (Universitas Murni Teguh, 2026)
Hypertension is one of the most common diseases in the community. This disease is included in the group of major non-communicable diseases worldwide, which can have a significant impact on various health problems, such as heart disease, stroke, kidney failure, disability, and premature death. There are two approaches to lowering blood pressure in people with hypertension: pharmacological and non-pharmacological methods. One approach is through complementary therapy, a foot soak using lemongrass and salt boiled water, which works through vasodilation, increased peripheral circulation, a relaxing effect, and decreased sympathetic nerve activity. This study aimed to determine the effect of a foot soak using lemongrass and salt boiled water on lowering blood pressure in people with hypertension in Sampali Village, Percut Sei Tuan District, Deli Serdang Regency. This study was quantitative, using a pre experimental method with a one-group pretest-posttest design. In this design, the researchers used one intervention group. A total of 25 respondents were selected using a purposive sampling technique. Data analysis was performed using the Wilcoxon signed-rank test. The results of this study using the Wilcoxon Signed-Rank Test showed a p-value of 0.000 (p <0.05), indicating a significant difference between blood pressure before and after the intervention, indicating a significant effect of foot soaks using lemongrass and salt boiled water on lowering blood pressure in hypertensive patients. Foot soaks using lemongrass and salt boiled water are effective in lowering blood pressure in hypertensive patients and can be implemented as a non-pharmacological therapy in the management of hypertension in healthcare facilities.